2020
DOI: 10.3390/molecules25173811
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue “Volatile Compounds and Smell Chemicals (Odor and Aroma) of Food”

Abstract: Among the constituents of food, volatile compounds are a particularly intriguing group of molecules, because they give rise to odour and aroma [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Volatile compounds found in the product were assessed using a sense of smell tool by capturing volatile compounds (Aprea 2020). The results of the scent hedonic test are statistically different.…”
Section: Hedonic Testmentioning
confidence: 99%
“…Volatile compounds found in the product were assessed using a sense of smell tool by capturing volatile compounds (Aprea 2020). The results of the scent hedonic test are statistically different.…”
Section: Hedonic Testmentioning
confidence: 99%
“…Drying also aims to remove moisture content up to 95-97% to maximize shelf life [14]. Drying using microwave ovens has very successful applications in food processing, especially in maintaining the quality of foodstuffs [15][16][17]. Even the usage of microwaves is considered to minimize energy consumption [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Milk produced by goats that have been administered with natural supplements has also been evaluated regarding its quality and sensory characteristics. Most studies, however, focused on the impact of ruminants' diet on the volatile flavor compounds, mainly in ripening cheeses made from cow milk [16]. Stefanon et al [17] found the effect of grass silage on the increase in keto odor compounds (3-butanedione, 2-butanone, 2-hexanone, 2-heptanone and 2-methyl-1-butanol) in Montasio ripening cheeses.…”
Section: Introductionmentioning
confidence: 99%